Selection for reluctance to avoid humans during the domestication of mice. (7th October 2013) - Goto, T.; Tanave, A.; Moriwaki, K.; Shiroishi, T.; Koide, T.
Abstract : Many animal species have been domesticated over the course of human history and became tame as a result of domestication. Tameness is a behavioral characteristic with 2 potential components: (1) reluctance to avoid humans and (2) motivation to approach humans. However, the specific behavioral characteristics selected during domestication processes remain to be clarified for many species. To quantify these 2 different components of tameness separately, we established 3 behavioral tests: the 'active tame', 'passive tame' and 'stay‐on‐hand' tests. We subjected genetically diverse mouse strains to these tests, including 10 wild strains (BFM/2Ms, PGN2/Ms, HMI/Ms, BLG2/Ms, NJL/Ms, KJR/Ms, SWN/Ms, CHD/Ms, MSM/Ms and CAST/Ei), a fancy strain (JF1/Ms) and 6 standard laboratory strains (C3H/HeNJcl, CBA/J, BALB/cAnNCrlCrlj, DBA/2JJcl, 129 +Ter /SvJcl and C57BL/6JJcl). To analyze the effects of domestication, these 17 strains were divided into 2 groups: domesticated strains (fancy and laboratory strains) and wild strains. Significant differences between strains were observed in all traits, and the calculated estimates of broad‐sense heritability were 0.15–0.72. These results illustrate that tameness in mice is significantly influenced by genetic background. In addition, they clearly show the differences in the features of tameness in domesticated and wild strains. Most of the domesticated strains showed significantly greater reluctance to avoid humans than wild strains, whereas there was no significant difference in the level of motivation to approach humans between these 2 groups. These results might help to clarify the genetic basis of tameness in mice . Abstract : Comparison of behavior in wild and laboratory mice using novel tame tests showed the characteristics of tameness.